Selection Of T Cell Receptor-Like Antibody Reactive To Mycobacterium Tuberculosis 16 Kda Heat Shock Protein From A Human Antibody Phage Display Library - Dass, Sylvia Annabel (2019)
T cell receptor (TCR)-like antibody has drawn the attention of many researchers recently due to its dual functionality of sandwiching the best of the humoral (antibody) and cell-mediated immunity (T cell) in a single platform. This is possible through the advancement in technology, specifically genetic engineering and phage display. The primary focus of this study was to generate TCR-like antibody for the development of latent tuberculosis diagnostics and therapeutics since the global burden contributed by latent tuberculosis is constantly increasing. As targets, Mycobacterium Tuberculosis (Mtb) heat shock protein (HSP) 16kDa antigen peptide presented by the major histocompatible complex (MHC) HLA-A*2, HLA-A*11 and HLA-A*24 were used in this study. The 16 kDa antigen heat shock protein is responsible for the survival of the TB bacilli during dormancy, making the protein a suitable candidate for latent tuberculosis investigation. Target peptide-MHC complexes were generated via a UV-mediated peptide exchange process. Prior to peptide exchange, UV-sensitive photolabile peptide-MHC complex of all three HLAs were formed by refolding each of the HLA heavy and β2M light chains along with a UV-sensitive peptide. Upon UV exposure, the photolabile peptide was cleaved at the UV-sensitive amino acid site allowing the exchange of 16 kDa antigen target peptide to form the 16 kDa target peptide-MHC complex.